Simultaneously optimizing pore morphology and enhancing mechanical properties of Al-Si alloy composite foams by graphene nanosheets. (28th February 2022) - Li, Weiting; Yang, Xudong; Yang, Kunming; He, Chunnian; Sha, Junwei; Shi, Chunsheng; Mei, Yunhui; Li, Jiajun; Zhao, Naiqin
Highlights: The 0.4 wt% GNSs/Al-Si composite foam sshow the energy absorption capacity of 6.8 ± 0.7 MJ/m 3 . The graphene nanosheets could provide more pore nucleation sites and protect the liquid films. The growth of Si precipitates was pronounced inhibited by the graphene nanosheets. Abstract: The integrity and regularity of pore morphology play an important role in determining the mechanical properties of the metallic foam materials. The conventional methods on refining pore morphology are mainly focused on the optimization of fabrication techniques, however, they are usually inconvenient and complicated. Recently, incorporating nano reinforcement is considered to be a suitable way to fabricate metallic composite foams accompanied by optimized pore morphology and enhanced mechanical properties. In this work, through a facile and rapid powder metallurgy foaming method, the aluminum-silicon (Al-Si) alloy composite foams reinforced by graphene nanosheets (GNSs) are successfully fabricated. The microstructure analyses reveal that, for the Al-Si alloy foams incorporating the GNSs (GNSs/Al-Si composite foams), the pore size is transformed to be smaller, the pore size distributions become more homogeneous and the pore shape is also refined to a regular and roundish state. Meanwhile, the shape of Si precipitates is found transforming from an irregular long strip (length of 20 μm, width of 5 μm) to a fine particle state (diameter of 5 μm). Moreover, the compressive testing results show that, the 0.4 wt% GNSs/Al-Si composite foams own the optimal compression stress of 11.7 ± 0.5 MPa, plateau stress of 10.0 ± 1.0 MPa and energy absorption capacity of 6.8 ± 0.7 MJ/m 3, which have improvement of 58.1%, 53.8% and 51.1% in comparison with the Al-Si alloy foams counterpart, respectively. The present findings may pave a new way for developing new generation of metallic composite foams that with stable microstructure and excellent mechanical performance. Graphical abstract: Image, graphical abstract